61 Investigating the smokers paradox by gender: differences in survival following acute st-?segment elevation myocardial infarction. (5th June 2017) - Steele, Lloyd; Palmer, James; Lloyd, Amelia; Fotheringham, James; Iqbal, Javaid; Grech, Ever D
Abstract : Background: The smoker's paradox, where smokers have better survival after acute myocardial infarction, was predominantly observed in the thrombolytic era. Evidence for the smoker's paradox in the current era of primary percutaneous coronary intervention (PCI) therapy is limited and inconsistent. Furthermore, there is no data regarding gender differences relating to this phenomenon. Methods: Data were collected for all patients with acute STEMI undergoing primary PCI at South Yorkshire Cardiothoracic Centre, UK between 2009 and 2014. Cox regression analysis was used to assess differences in survival (at 30 days, 1 year, and 3 years) by smoking status and gender after adjustment for confounding factors. Results: There were 2726 STEMI patients (26.4% female) during the study period. Male patients were younger than females (61.0±12.1 vs 65.5±13.1 years, p=0.02). Smoking prevalence was similar in both genders (males 48.3%, females 48.0%), but a greater proportion of females had never smoked (27.8% vs 21.0%, p=0.01). Male current smokers had a significantly worse 3 year mortality than never smokers (HR 1.51, 95% CI 1.04–2.21, p=0.03). In female patients smoking status had no significant effect on survival (p=0.58), which could potentially be due to the modest number (n=723) of female patients in this study. Overall survival was similar in both males and females (p=0.72). Conclusions: There was no evidence of a smoker's paradox in STEMI patients followed up to 3 years in either males or females.